Phase dependent encapsulation and release profile of ZIF-based biocomposites. Issue 13 (20th February 2020) - Carraro, F.; Velásquez-Hernández, M. de J.; Astria, E.; Liang, W.; Twight, L.; Parise, C.; Ge, M.; Huang, Z.; Ricco, R.; Zou, X.; Villanova, L.; Kappe, C. O.; et al.
Abstract : We report two ternary phase diagrams that show the synthesis conditions to prepare protein@ZIF biocomposites with different phases, including BSA@ZIF-C and insulin@ZIF-C. For each biocomposite, we measured distinct encapsulation efficiency and release profile properties. Abstract : Biocomposites composed of Zeolitic Imidazolate Frameworks (ZIFs) are generating significant interest due to their facile synthesis, and capacity to protect proteins from harsh environments. Here we systematically varied the composition ( i.e. relative amounts of ligand (2-methylimidazole), metal precursor (Zn(OAc)2 ·2H2 O), and protein) and post synthetic treatments ( i.e. washes with water or water/ethanol) to prepare a series of protein@ZIF biocomposites. These data were used to construct two ternary phase diagrams that showed the synthesis conditions employed gave rise to five different phases including, for the first time, biocomposites based on ZIF-CO3 -1. We examined the influence of the different phases on two properties relevant to drug delivery applications: encapsulation efficiency and release profile. The encapsulation efficiencies of bovine serum albumin and insulin were phase dependent and ranged from 75% to 100%. In addition, release profiles showed that 100% protein release varied between 40 and 300 minutes depending on the phase. This study provides a detailed compositional map for the targeted preparation of ZIF-based biocomposites of specific phases and a tool for the straightforward analysis of the crystalline phases of ZIF based materials (web application named "ZIF phase analysis"). These data will facilitate the progress of ZIF bio-composites in the fields of biomedicine and biotechnology.